2022
DOI: 10.33448/rsd-v11i5.28144
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of femur and humerus at the three-point bending and axial compression tests in the crab-eating fox (Cerdocyon thous, Linnaeus 1776)

Abstract: The aim of the present study was to evaluate the mechanical behaviour of the femur and humerus of Cerdocyon thous through three-point bending and axial compression tests. For this, 13 femurs and 15 humerus were used in the bending test, and 14 femurs and 15 humerus in the compression test; after the assays were completed, bone fragments were collected for evaluation by means of conventional optical and polarized light microscopy, and scanning electron microscopy. It was observed that the humerus is more resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When compared to the properties of cancellous and cortical bones, it is known that flexural strength can vary due to various factors such as age, gender, bone density, and anatomical location ( Pastor et al, 2022 ). Within this context, the study by F. Pastor et al evaluated bones of canids ( Cerdocyon thous ) through three-point bending tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to the properties of cancellous and cortical bones, it is known that flexural strength can vary due to various factors such as age, gender, bone density, and anatomical location ( Pastor et al, 2022 ). Within this context, the study by F. Pastor et al evaluated bones of canids ( Cerdocyon thous ) through three-point bending tests.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the average flexural strength for the humerus was 7.4 MPa, while for the femur, it was 5.5 MPa. Additionally, bone length, weight, and width influence mechanical behavior ( Pastor et al, 2022 ). In the article by J. Lotz et al, a quantitative study on the mechanical properties of human cancellous bones was conducted, indicating estimated strengths of approximately 15 MPa ( Lotz et al, 1990 ).…”
Section: Discussionmentioning
confidence: 99%